(untitled) (Религиски дијалог и соработка, 2024)
Rational the relationship of globalization with social institutions, focusing on the term of globalization of modernity, religion and religious phenomena are of unavoidable interest. Interest in religious phenomena is on the rise, and globalization as such is multifaceted. Never before have there been so many nonreligious people in human history, as well as never before in human history has there been so much religious population on the planet. Globalization and religion are linked through the following aspects: religious diversity is on the rise, the difference at the level of organization is increasing, as well as that the subjective religiosity is being strengthened. The mentioned aspects are theoretically based on the globalization of modernity, which implies the aspects of the diffusion of processes, as well as the dynamics, which are typically modern in nature and extend to the world level even in their influence. As the most typical modern processes and dynamics are: speed, widespread and continuous process of transformation of society, structural difference, detraditionalization, and individualization. Undoubtedly, the enumerated processes of modern globalization have their impact on religion. The aim of this article is to theoretically elaborate the indicated aspects through a review of the relevant literature. The theoretical framework will be used as a concept or further empirical research on the connection between religion and globalization.